#Balkanization: A Critical Study of Otherness through Twitter - Veliu, Liridona (Masters of Peace,, 2018)
Liridona Veliu examines 'balkanization' as a long-standing discourse of identity construction, otherness and stereotyping through Twitter. Although deriving from the Balkans and attached to the Balkan Peninsula, the 'balkanization' discourse has gained a life of its own. The author challenges its current manifestations shaped by the era of social media and identifies and connects its meanings with deeper processes of historical events. This book denaturalizes 'balkanization' as a constructed source of knowledge, approaching the topic embedded in genealogy and deconstructivism, and applies critical discourse analysis as a method of research. Contents Deconstructing the 'Balkanization' Discourse 'The Balkans' through Genealogy Twitter Mechanism and Data Collection Critical Discourse Analysis Archetypes of Subjectivities Target Groups Lecturers and students of psychology, political science, peace and conflict studies, sociology Practitioners and researchers in the fields of peace work, international relations, corpus linguistics, media and communication The Author Liridona Veliu is a peace researcher from the MA program in Peace, Development, Security and International Conflict Transformation at the University of Innsbruck, Austria. She is currently a PhD student at the School of Law and Government at Dublin City University. Congruently, she is supporting the Erasmus+ European Commission funded project on the creation of the graduate curricula in Peace Studies in Georgia (PESTUGE) as part of the University of Innsbruck staff.